Peranan Motivasi Dalam Meningkatkan Kinerja Pegawai Pada Unit Pelaksanaan Teknis Daerah Pusat PelayananTerpadu Pemberdayaan Perempuan Dan Anak (UPTD P2TP2A) Tangerang Selatan - Rahman, Ana Septia; Finus, Reneldis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to determine the effect of work discipline on employee This study aims to analyze how the motivation in improving employee performance at the Regional Technical Implementation Unit of the Integrated Service Center for the Empowerment of Women and Children (UPTD P2TP2A). With the title the role of motivation in improving employee performance at the Regional Technical Implementation Unit of the Integrated Service Center for the Empowerment of Women and Children (UPTD P2TP2A). This study used descriptive qualitative method. The unit of analysis is an employee at UPTD P2TP2A. The data collection methods used were observation, in-depth interviews with key informants, focus group discussions, study documentation, literature and SWOT analysis. The collected data were analyzed descriptively with the following lines: (1) data reduction; (2) data presentation; and (3) checking the validity of the data. In order to obtain the validity of the data, an analysis was carried out through (1) internal validity (2) external validity and (3) reliability. From the results of this study, it can be said that, from the results of interviews with key informants, giving as a whole is very important to improve employee performance effectively and efficiently. However, physiological offerings such as being able to eat and drink and the need for appreciation have not been met properly. Meeting the physiological needs of employees is very important in improving employee performance. With the fulfillment of physiological needs can increase employee motivation and employee performance can increase well. The application of motivation in the Regional Technical Implementation Unit of the Integrated Service Center for the Empowerment of Women and Children (UPTD P2TP2A) can improve employee performance. With high employees, everything that is done can be done well. The strategy is implemented under conditions that are very supportive of an aggressive growth policy.